PENGARUH LAPORAN HASIL PEMERIKSAAN, KETIDAKPATUHAN PADA PERATURAN, KELEMAHAN SISTEM PENGENDALIAN INTERN, DAN TINDAK LANJUT TERHADAP KINERJA KEUANGAN PEMERINTAH DAERAH SUMATERA SELATAN - Rina Tjandrakirana; Ermadiani Ermadiani; Abdul Rohman; Ahmad Widad (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2019)
This study aims to see reports on the results of examinations, non-compliance with SPI, non-compliance with laws and follow-up checks that affect or not on the financial performance of local governments. We need to do this because there are many recent events related to the capture of local government organizers in relation to the financial management of local governments. This study uses a population of all Local Governments in the South Sumatra Province. Regional Governments consist of Provinces, Regencies, and Cities. The number of Regional Governments is 18 Regional Governments. By using secondary data in the form of financial statements consisting of budget realization reports, balance sheets, cash flow reports researchers examine the independent variables and dependent variables using multiple regression techniques. The data is a panel of data for 3 years from 2014, 2015 and 2016. The results of the research found are that the research model is feasible to use, the general influence of independent variables on the dependent variable is not strong (weak). The direction of the relationship is in the opposite direction. Thus the alternative hypothesis is rejected and the null hypothesis is accepted.